The Influence of Transformational Leadership on Employee Performance at CU Sauan Sibarrung Tana Toraja - La'biran, Dian Tiku Rombe; Tandirerung, Ch. Jeane; Londong, Jerliyen Pramita (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
Study This aiming For analyze influence leadership transformational to performance employees at Sauan Credit Union Sibarrung Tana Toraja. Research use approach quantitative with data collection through questionnaire against 20 employees remain . Data analysis was performed using the Pearson correlation test , the coefficient determination , and t-test through SPSS application . Research results show that leadership transformational influential positive and significant to performance employees , with mark correlation of 0.606 and the contribution influence by 34.5%. Findings This strengthen that dimensions leadership like charisma , motivation inspiring , stimulating intellectual , and individual attention real increase quality work , responsibility answer , and initiative employees . This study recommend importance strengthening style leadership transformational in managerial strategies to create environment productive , innovative and sustainable work . These results can made into base for development policy leadership in cooperative and institution finance based on community .